Предмет: Алгебра,
автор: nursultana442
(sinA+cosA)*(sinB-cosB)=sin (B-A)-cos (B+A)
Ответы
Автор ответа:
0
sinAsinB-sibAcosB+cosAsinB-coaAcosB=
=(cosAsinB-sinAcosB)-(coaAcosB-sinAsinB)=sin(B-A)-cos(A+B)
=(cosAsinB-sinAcosB)-(coaAcosB-sinAsinB)=sin(B-A)-cos(A+B)
Автор ответа:
0
спасибо большой
Автор ответа:
0
Похожие вопросы
Предмет: Геометрия,
автор: Anyhka12
Предмет: Математика,
автор: azelya15
Предмет: География,
автор: lord12345top4ik
Предмет: Химия,
автор: Аноним
Предмет: Математика,
автор: nastyaust2002